Obtaining vital distances using wearable inertial measurement unit for real-time, biomechanical feedback training in hammer-throw - Wang, Y.; Li, H.; Wan, B.; Zhang, X.; Shan, G. (Applied Sciences, 2018)
The hammer throw is one of the regular track and field competitions, but unlike other events, it has not seen a new world record for over three decades. The standstill may be caused by the lack of scientifically based training. In our previous work, we have developed a wireless/wearable device for the wire tension measurement in order to develop real-time biomechanical feedback training. In this paper, we show the improvement of our wearable system by adding two sensors for tracking of two vital vertical distances. The paper describes the details related to the development of turning an inertial measurement unit into a tracking device for the dynamic distances. Our preliminary data has shown that the dynamic data of the hip and wrist could be used for revealing the coordination between the upper and the lower limbs during a throw. In conjunction with wearable wire-tension measurement, various motor control patterns employed for hammer throwing could be demystified. Such real-time information could be valuable for hammer-throw learning and optimization. Further studies are required to verify the potentials of the wearable system for its efficiency and effectiveness in coaching practice.